Precoating aplicado nos meios filtrantes para aumentar a eficiência de coleta dos filtros mangas de uma indústria siderúrgica - Aranha, Renan Paulo Marques Alves (Universidade Federal de São Carlos, 2020)
Bag Filter is a device widely used in industries to control the emission of pollutants in the air. This equipment has high efficiency for micrometric particles and application in different types of processes, in addition to having low operating costs. To increase the efficiency of collecting microparticles (0.5 to 3 μm), some industries are using pre-coating or precoating, to fill the pores of the filter medium with particles, in order to improve the filtration performance and prolong the sleeve life. Thus, the present work proposed to study the effect of precoating on the filtration efficiency, during the filtration of the powder from the steelworks of a steel industry. All the particulate materials used, the precoatings and the powder of the steel mill, were characterized in relation to the specific mass and the average volumetric diameter. The tests, for the evaluation of the emission of particulates, were carried out using an experimental apparatus based on the VDI 3926 standard, whose operational conditions considered standard refers to a filtration speed of 2 m / min, the concentration of particulate material close to the filter of 5000 g / L, the excess pressure in the 500 kPa compressed air tank and the cleaning air pulse time of 60 ms. Therefore, the tests showed that the filtering media with precoating achieved higher efficiency than the PTFE membrane for particles smaller than 3 μm. Talc, the precoat, with the best performance. In addition, the maximum pressure drop of 20 mmH2O obtained a collection efficiency close to 100% without significant variations for the aerodynamic diameter range studied with 10% talc mass mixture.
Precoating applied in the filter media to increase the collection efficiency of bag filters in a steel industry
Keywords: Filtros de mangas, Filtração de gases, Material particulado, Poluição do ar, Precoating, Bag Filters, Gas filtration, Filter media, Dust; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA